Art and Architecture: Democratising and Conceptualising Artistic Space in Cape Towns De Waterkant - Maritz, Grethe (School of Architecture, Planning and Geomatics, 2023)
This investigation focusses on the relationship between art and architecture, as investigated through conceptual and social lenses, to culminate in the design of an inclusive arts centre in Cape Town's De Waterkant, as a gentrified, layered urban context. Firstly, the relationship between art and architecture is considered in terms of the potential to utilise artistic principles and ideas in architectural space-making. I explore the translation of several stages and elements of the artistic process as architectural informants. I investigate not only how the conception, production, consumption, and representation of art can inform architectural design, but also, from a more literal standpoint, the theory and making of collaborative programmes, spaces, and elements through engagement with artists that utilize different mediums and techniques in their work. Secondly, the elitist nature of the commercial art industry prompts the investigation into the social and public properties of art, with the investigation into public art and its relation to the building envelope and the city as a whole. The integration and role of art in the metropolitan context are studied to lead into the construction of a programmatic response that facilitates a more accessible, inclusive, and sustainable counterpoint to the conventional, exclusionary model. Artists and the local public are proposed as primary stakeholders of a programme and space that serves the public as opposed to the elite. All these investigations culminate in the development of an experimental architectural response that, in crafting the spatial and material, aims to consider both the conceptual and social relationship between art and architecture.